Application of narrative nursing for patients undergoing intravesical chemotherapy for carcinoma of the bladder (叙事护理在膀胱癌局部灌注化疗患者中的应用) - ZHANG Dan (张丹); CHEN Jianying (陈建英) (中西医结合护理)
Objective To investigate the effect of narrative nursing for patients undergoing intravesical chemotherapy for carcinoma of the bladder. Methods Totally 260 patients undergoing intravesical chemotherapy for carcinoma of the bladder were divided into control and study group. All patients received routine care during the perioperative period, and those in the study group were given narrative nursing. The mental status, quality of life and incidence of bladder irritation were compared between two groups. Results The scores of Hamilton Rating Scale for Depression(HAMD) and Hamilton Rating Scale for Anxiety(HAMA) decreased in both two group after intervention, and scores of HAMD and HAMA in the study group were lower than those in the control group (P＜0. 05). The subscale score and total score of quality of life assessment in the study group were higher than those in the control group after nursing intervention(P＜0. 05). The incidence of bladder irritation was 3. 08%(4/130) in the study group, which was lower than 15. 38%(20/130) in the control group (P＜0. 05). Conclusion Narrative care during intravesical chemotherapy can effectively improve the patient mental status and quality of life, reduce the incidence of bladder irritation, and enhance the effect of chemotherapy. (目的 探讨叙事护理在膀胱癌局部灌注化疗患者中的应用效果。方法 260例行局部灌注化疗的膀胱癌患者随机分为对照组与研究组, 各130例。对照组给予常规护理干预, 研究组在对照组基础上实施叙述护理干预。评估2组干预前后心理状况, 比较2组干预后生活质量, 记录2组膀胱刺激症发生情况。结果 干预后, 2组汉密顿抑郁量表(HAMD)、汉密尔顿焦虑量表(HAMA)评分均较干预前降低, 且研究组评分低于对照组, 差异有统计学意义(P＜0. 05)。研究组生活质量调查量表各维度评分及总评分均高于对照组, 差异有统计学意义(P＜0. 05)。研究组膀胱刺激症发生率3. 08%(4/130), 低于对照组的15. 38%(20/130), 差异有统计学意义(P＜0. 05)。结论 膀胱癌局部灌注化疗患者化疗干预期间接受叙事护理, 可有效缓解不良情绪, 提高生存质量, 降低膀胱刺激症发生风险。)